Endoscopic Posterior Cricoid Split With Graft in an Adult With Posterior Cricoid Fracture. (12th September 2018) - Zhou, Albert H.; Patel, Varesh R.; Hsueh, Wayne D.; Paskhover, Boris; Kaye, Rachel
Abstract : A 45‐year‐old man presented with bilateral vocal fold immobility (BVFI) following a remote history of assault. He was found to have a comminuted, telescoped, and ossified posterior cricoid fracture on imaging. Electromyography revealed normal cricothyroid and thyroarytenoid muscle function, but moderate chronic denervation of bilateral posterior cricoarytenoid muscles. The patient underwent endoscopic posterior cricoid split with rib graft (EPCS/RG), and he regained moderate vocal abduction and full vocal adduction, resolution of dysphonia, and was decannulated. This report describes the only case of an adult with BVFI due to a posterior cricoid fracture that was successfully treated with EPCS/RG. Laryngoscope, 128:2864–2866, 2018